PEMBELAJARAN E-LEARNING PADA MATA PELAJARAN PAI DI SD NEGERI 1 PANDEGLANG: Studi Kasus di SD 1 Muruy Pandeglang Banten - M. Muslim (LPPM Universitas Bina Bangsa, 2023)
Learning is a human need that must be met under any circumstances, including during the Covid-19 pandemic which required distance learning (PJJ). For this reason, the majority of schools organize online learning using e-learning, and SD Negeri 1 Muruy is no exception. e-learning which is electronic-based learning both online and offline has obstacles.This study aims to 1) Assess the design of e-learning learning plans in PAI Subjects at SD Negeri 1 Muruy Pandeglang Banten; 2) Assessing the implementation of e-learning learning in PAI subjects at SD Negeri 1 Muruy Pandeglang Banten Public Middle School; 3) Reviewing the implementation of e-learning learning evaluation in PAI subjects at SD Negeri 1 Muruy Pandeglang Banten Public Middle School; 4) Analyzing the results of the implementation of learning PAI subjects at SD Negeri 1 Muruy Pandeglang Banten. This study uses a qualitative method with a phenomenological approach. The results of the study show that the design of e-learning learning plans for PAI Subjects at SD Negeri 1 Muruy Pandeglang Banten is to prepare CBT/CBE applications, prepare student and teacher accounts to access CBT/CBE, arrange full online learning schedules or shift systems, compile RPP blended, holding training related to e-learning and installing CBT/CBE replacement applications. The implementation of e-learning learning in PAI subjects was mostly carried out online which initially used the CBT Al Fattah application, then changed to using WAG which included links to other applications, such as Zoom, Google Meet, Plif Book, Youtube, PPt and Podcast for audio. . Implementation of e-learning learning evaluations using the CBT Application or Google Form, E-mail, or Youtube, both Daily Assessments, Formative Tests and Summative Tests. Based on the documentation study of PTS report cards, it shows that the cognitive value of students in PAI Subjects increases when face-to-face learning, on the contrary when PJJ, there are more scores below the KKM. Therefore, it is necessary to improve the quality of e-learning learning in PAI Subjects